Stadium, Diagnosis, dan Tatalaksana Penyakit Alzheimer - Aditya Gloria Monalisa Sianturi (Majalah Kesehatan Indonesia, 2021)
Dementia is a general term for loss of memory that can occur along with behavioral or psychological symptoms in patients. The first cause of dementia patients is Alzheimer's disease. Alzheimer’s disease is a brain degenerative disease and the most common cause of dementia. In Alzheimer’s disease, there are three development stages, which is stage 1, stage 2, and stage 3 with different clinical symptoms at each stage. There are several clinical criteria for establishing a definitive diagnosis of Alzheimer’s disease and also support examinations have to be carried out. Until now, Alzheimer’s treatment has not been cured. Giving some pharmacotherapy only to reduce the progression of Alzheimer’s disease.   Demensia merupakan hilangnya ingatan yang bisa timbul bersama dengan gejala gangguan perilaku maupun psikologis pada seseorang. Penyebab pertama penderita demensia adalah penyakit Alzheimer. Penyakit Alzheimer adalah penyakit degeneratif otak dan penyebab paling umum dari demensia. Pada penyakit Alzheimer terdapat beberapa stadium perkembangan penyakit Alzheimer yaitu stadium 1, stadium 2, dan stadium 3 dengan gejala klinik yang berbeda di setiap stadium. Terdapat beberapa kriteria klinis dalam penegakan diagnosis definitif penyakit Alzheimer serta harus dilakukan pemeriksaan penunjang.  Pada tatalaksana penyakit Alzheimer hingga saat ini memang belum dapat disembuhkan, Pemberian obat-obatan hanya untuk mengurangi progresifitas penyakit Alzheimer.